Effect of cobalt content on electrochemical performance for La0.6Sr0.4CoxFe1-xO3-δ and BaZr0.8Yb0.2O3-δ composite cathodes in protonic ceramic fuel cells. Issue 12 (15th June 2023) - Watanabe, Konosuke; Yamaguchi, Yuki; Nomura, Katsuhiro; Sumi, Hirofumi; Mori, Masashi; Mizutani, Yasunobu; Shimada, Hiroyuki
Abstract: This study compares the electrochemical performance of the composite cathodes of La0.6 Sr0.4 Cox Fe1-x O3- δ and BaZr0.8 Yb0.2 O3- δ (BZYb) sintered at 900 and 1100 °C in anode-supported protonic ceramic fuel cells (PCFCs) using a BZYb electrolyte. For materials composited with BZYb, La0.6 Sr0.4 Co0.2 Fe0.8 O3– δ (LSCF), La0.6 Sr0.4 CoO3– δ (LSC), and La0.6 Sr0.4 FeO3– δ (LSF) were used. The composite cathodes sintered at 1100 °C showed higher performance than those sintered at 900 °C, because the number and thickness of proton conductive network paths of BZYb within the composite cathodes increase with increasing sintering temperature. The PCFCs with LSCF-BZYb, LSC-BZYb, and LSF-BZYb composite cathodes exhibit power densities of 0.25, 0.19, and 0.07 W cm −2, respectively, at an operating temperature of 600 °C. The polarization resistance of the Co-free LSF-BZYb composite cathodes is originally higher than those of the Co-containing LSC-BZYb and LSCF-BZYb cathodes, suggesting that Co plays an important role in obtaining high catalytic activity for cathode reactions in PCFCs as well as conventional solid oxide fuel cells.